2010
DOI: 10.1186/cc9354
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 blockade improves survival in experimental sepsis by inhibiting lymphocyte apoptosis and reversing monocyte dysfunction

Abstract: IntroductionLymphocyte apoptosis and monocyte dysfunction play a pivotal role in sepsis-induced immunosuppression. Programmed death-1 (PD1) and its ligand programmed death ligand-1 (PD-L1) exert inhibitory function by regulating the balance among T cell activation, tolerance, and immunopathology. PD-1 deficiency or blockade has been shown to improve survival in murine sepsis. However, PD-L1 and PD-1 differ in their expression patterns and the role of PD-L1 in sepsis-induced immunosuppression is still unknown.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
210
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(239 citation statements)
references
References 35 publications
12
210
3
6
Order By: Relevance
“…However, our findings of reduced T cell responses mediated by PD-L1 on B. pseudomalleiinfected PMNs are consistent with the increasing involvement of this pathway in regulating antimicrobial responses to acute infections (24,37). This is strongly supported by a report demonstrating that IFN-g-stimulated neutrophils after acute inflammatory responses suppress T cell function via their expression of PD-L1 on neutrophils (21).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, our findings of reduced T cell responses mediated by PD-L1 on B. pseudomalleiinfected PMNs are consistent with the increasing involvement of this pathway in regulating antimicrobial responses to acute infections (24,37). This is strongly supported by a report demonstrating that IFN-g-stimulated neutrophils after acute inflammatory responses suppress T cell function via their expression of PD-L1 on neutrophils (21).…”
Section: Discussionsupporting
confidence: 81%
“…blockade of the PD-1 pathway decreased mortality in clinically relevant animal models of bacterial sepsis (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common to most septic patients is the increased expression of PD‐1 on T cells during the progression from hyper‐inflammation to hypo‐inflammation. Recent studies showed that disruption of the PD‐1/PD‐L1 axis either by genetic deletion or by pharmacological manipulation improves survival in bacterial and fungal murine sepsis 46, 47. Boomer et al showed that PD‐1 expression was increased in CD4 and CD8 T cells, whereas PD‐L1 expression was increased in antigen‐presenting cells as well as in the spleen and lungs of septic patients.…”
Section: Immunological Modification Therapiesmentioning
confidence: 99%
“…Recent studies have reported that PD-L1 expression also increased in mice with sepsis induced by CLP (12,36). Additionally, blockade of PD-L1 by antibody suppressed intestinal inflammation and prevented the development of colitis in mice (13) …”
Section: Junction Integritymentioning
confidence: 99%